Fundamentals of astronomy - Barbieri, Cesare, 1942- (Taylor & Francis, 2007)
Providing a broad overview of foundational concepts, Fundamentals of Astronomy covers topics ranging from spherical astronomy to celestial mechanics, closing with two chapters that discuss elements of astronomical photometry and spectroscopy. Supplementary and explanatory notes at the end of each chapter provide references to material published in scientific journals, and solved and unsolved exercises allow students to review their understanding of the material. Broad in coverage, the book presents arguments from classical astronomy, such as spherical astronomy, that form the foundation for future work in the field.